Consumer preferences for lab-cultured and traditional meat in Ghana - REBECCA OWUSU (Smujo International, 2025)
Abstract. Owusu R. 2025. Consumer preferences for lab-cultured and traditional meat in Ghana. Asian J Agric 9: 483-497. There is a growing demand for meat as a source of protein in the human diet because of the increasing population. This has raised ethical and environmental concerns, highlighting the need for alternative protein sources, including lab-cultured meat. While interest in consumer preferences for alternative meat has grown globally, evidence from emerging economies like Ghana remains limited. This study investigates consumer preferences for alternative meat sources using a choice experiment approach. Specifically, the study aims to (i) assess baseline awareness of lab-cultured meat to identify public education needs, (ii) uncover cultural or economic barriers to adoption for targeted interventions, and (iii) quantify consumer preferences and willingness to pay to guide market pricing strategies. It employs a descriptive survey design, utilizing a sample of 265 consumers from the Cape Coast Metropolis, with data collected through questionnaires. The empirical specifications were estimated using a Bayesian mixed logit model in preference and willingness to pay (WTP) spaces to account for preference heterogeneity and improve WTP estimations. The econometric modeling results indicate that sampled consumers are price-sensitive, with affordability, limited availability, and low awareness emerging as the most significant barriers to consumption. Plant-based meat was positively valued in WTP space, while consumers generally are indifferent towards lab-cultured meat, which becomes more acceptable as an ethical and sustainable alternative, for the younger and higher income earners when socioeconomic interactions were incorporated, suggesting a heterogeneous but emerging market. Additionally, the results show that consumers prefer locally produced meat over imported meat, with origin being a key factor in their purchasing decisions. Furthermore, a low carbon footprint influences consumers' choice of meat alternatives. While the sample provides insights into urban consumer behavior, rural preferences may differ. The results suggest targeted marketing of lab-cultured meat as an ethical choice and support for local production to enhance acceptance.